Assessing the performance of alternative investments using non-parametric efficiency measurement approaches: Is it convincing? - Glawischnig, Markus; Sommersguter-Reichmann, Margit (Journal of Banking & Finance, 2010)
DEA-based performance assessment in the alternative investment fund industry is often motivated by the fact that DEA is capable of simultaneously handling multiple input (risk) and multiple output (return) measures, thereby still offering a single real number as a performance index without utilizing subjective weights to aggregate these inputs and outputs. This paper aims at investigating whether DEA-based performance indexes previously used to assess alternative investment fund performance are actually able to satisfy these properties, and to contrast the findings using a DEA-based performance index with those using a traditional financial performance index.